Method for enhancing zinc powder replacement activity in zinc powder purification and copper and cadmium removal process through ultrasonic waves

By using ultrasonic technology and dilute sulfate slurry zinc powder in zinc-baked neutral leaching solution, the problem of adjusting the pH value or increasing the temperature of copper and cadmium in zinc-baked neutral leaching solution in the prior art is solved, and the effect of efficiently removing copper and cadmium under normal temperature and pressure is achieved.

CN119614895APending Publication Date: 2025-03-14KUNMING UNIV OF SCI & TECH +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510030629.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the prior art, when removing copper and cadmium from zinc-baked sand neutral leaching liquid, the pH value needs to be adjusted or the temperature is increased, resulting in an increase in zinc powder usage and high energy consumption, and it is difficult to achieve efficient removal without changing the pH value and increasing the temperature.

Method used

Ultrasonic technology is used to replace copper and cadmium in the zinc powder slurry liquid. By diluting zinc slurry zinc powder, the pH value of the zinc powder slurry liquid is adjusted to be consistent with the neutral leaching liquid of zinc baked sand, and the zinc powder slurry liquid is added in batches under ultrasonic conditions to achieve efficient removal of copper and cadmium.

Benefits of technology

Without changing the pH value and increasing the temperature, the zinc powder usage is reduced by 26-35%, the reaction time is shortened by 50%, and the copper and cadmium discharge rate is achieved. The entire process is clean and efficient, meeting the requirements of clean production and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614895A_ABST
    Figure CN119614895A_ABST
Patent Text Reader

Abstract

The invention relates to a method for enhancing the replacement activity of zinc powder in the zinc powder purification and copper and cadmium removal process through ultrasonic waves, and belongs to the technical field of zinc calcine neutral leachate impurity removal. Industrial hydraulic atomized zinc powder is used as a raw material for replacing copper and cadmium, and copper and cadmium are removed through replacement with the zinc powder under the ultrasonic condition; according to the present invention, the copper and the cadmium are removed under the conditions of the pH value of 5.0-5.4 and the room temperature, the amount of the zinc powder is reduced by 26-35%, the standard cadmium and copper removal rate can still be obtained, the replacement reaction time is shortened by 50%, the high precipitation rate of the copper and the cadmium is achieved with the low amount of the zinc powder and the low reaction temperature, and the method is suitable for industrial production. And the purified zinc calcine neutral lixivium is directly sent to an electrodeposition process without adjusting the pH value, so that the production cost is greatly reduced. In addition, the whole process is clean and efficient, and meets the requirements of clean production and environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of impurity removal of zinc roasted sand neutral leaching solution, and specifically relates to a method for enhancing the replacement activity of zinc powder in the process of zinc powder purification and copper and cadmium removal by using ultrasonic wave. Background Art

[0002] The neutral leachate of zinc roasted sand is the raw solution for electrolytic zinc deposition. It needs to be purified before electrolytic deposition. The presence of copper and cadmium will affect the electrolytic deposition process. During the electrolytic deposition process, copper ions will be deposited on the cathode before zinc ions to form copper-zinc alloys, which not only reduces the zinc deposition efficiency, but also causes uneven electrode surface and affects product quality. In addition, copper ions are highly corrosive to the materials of the electrolytic cell. Long-term accumulation will shorten the service life of the equipment and increase the cost of maintenance and replacement. Cadmium is a toxic heavy metal. It is not only biologically toxic, but also accumulates slowly in the environment. Long-term pollution may have serious effects on aquatic organisms, animals and human health. The presence of cadmium ions in the zinc electrolytic deposition process will not only affect the purity of the zinc product, but also have a certain corrosive effect on the electrolytic cell materials, especially in some application fields with strict requirements on cadmium content, such as battery manufacturing, coatings, etc., and will accelerate the aging and damage of the equipment. Therefore, effectively removing copper and cadmium from the neutral leachate of zinc roasted sand is not only necessary to improve the quality and production efficiency of zinc products, but also a necessary measure to protect the environment and protect the health of workers, which has important economic and environmental significance.

[0003] In order to eliminate the influence of copper and cadmium on zinc electrowinning, domestic and foreign scholars have developed a variety of effective purification and impurity removal technologies for zinc sulfate solution in the process of wet zinc smelting, such as chemical precipitation, solvent extraction, adsorption, electrochemical and microbiological methods. Although the above methods can effectively remove impurities such as copper and cadmium from zinc sulfate solution, they still face severe challenges in the face of expanded industrial production. For example, the chemical precipitation method has more by-products, the separation and treatment process of the precipitate is relatively cumbersome, and the treatment of the precipitate may cause secondary pollution to the environment. The solvent recovery and regeneration process in the solvent extraction method is relatively complicated, and may cause environmental pollution problems of organic solvents. The electrochemical method faces low current efficiency and high energy consumption. The microbial method has high costs for microbial cultivation and treatment, and the processing speed is slow. The zinc powder replacement method is a general method for wet zinc smelting enterprises to purify Cu and Cd from zinc sulfate solution. This method is based on the difference in the standard electrode potential of the metal, and uses zinc powder to replace impurity ions from the solution to generate insoluble metal precipitates. The advantages of this method are simple operation and low cost, and it is suitable for treating zinc sulfate solution with high impurity concentration. Generally, the zinc powder replacement efficiency can be improved at a lower pH value and a higher reaction temperature. However, since the optimal pH value for zinc electrowinning is 5.0-5.4, if the pH value is lowered to replace copper and cadmium, alkali needs to be added after the replacement to adjust the pH value of the neutral leachate of zinc roasted sand and then sent to the electrowinning process. This requires the increase of production equipment and raw material consumption in the actual production process. At the same time, if the reaction temperature is increased, it will inevitably produce higher energy consumption for large-scale production. Therefore, it is more in line with production practice to achieve the removal of copper and cadmium in the neutral leachate of zinc roasted sand without changing the pH value or increasing the temperature, but this also means an increase in the amount of zinc powder used and a decrease in the removal rate of copper and cadmium. Summary of the invention

[0004] In view of the problems existing in the background technology, the present invention provides a method for enhancing the replacement activity of zinc powder in the process of zinc powder purification and copper and cadmium removal by ultrasonic wave. Without changing the pH value of the neutral leachate of zinc roasted sand, the amount of zinc powder is reduced by replacing copper and cadmium with zinc powder under ultrasonic conditions. Experiments have shown that a lower temperature is more conducive to the precipitation of cadmium. The neutral leachate of zinc roasted sand after cadmium removal can be directly sent to the electrodeposition process. A higher copper and cadmium removal rate is achieved at a lower temperature, and the replacement time is shortened and the amount of zinc powder is reduced.

[0005] To achieve the above object, the present invention is implemented through the following technical solutions:

[0006] The method for enhancing the replacement activity of zinc powder by ultrasonic wave in the process of zinc powder purification and copper and cadmium removal comprises the following steps:

[0007] (1) slurrying zinc powder with dilute sulfuric acid, the pH value of the zinc powder slurry is 5.0-5.4;

[0008] (2) adding the zinc powder slurry into the neutral leaching solution of zinc roasted sand, and replacing and removing copper and cadmium under ultrasonic conditions, with the reaction temperature being 20-40° C.;

[0009] (3) liquid-solid separation to obtain a purified zinc roasted sand neutral leaching solution from which copper and cadmium are removed.

[0010] Furthermore, in the neutral leachate of zinc roasted sand, the copper ion concentration is 530-730 mg / L, and the cadmium ion concentration is 360-417 mg / L.

[0011] Furthermore, in step (1), the liquid-to-solid ratio of zinc powder to dilute sulfuric acid is 1-6:1, and the slurrying method is mechanical stirring.

[0012] Furthermore, in step (2), the zinc powder slurry is added in portions.

[0013] Furthermore, the last addition of zinc powder is 15-20 minutes away from the end of the reaction.

[0014] Furthermore, the amount of the pure zinc powder added is 1.8-4 times the total molar amount of copper and cadmium in the neutral leaching solution of zinc roasted sand.

[0015] Furthermore, the ultrasonic frequency is 19.4-19.8kHz, and the power is 30-600W.

[0016] Furthermore, the zinc powder is industrial hydraulic atomized zinc powder.

[0017] Beneficial effects of the present invention:

[0018] The invention uses the neutral leachate of zinc roasted sand with equivalent copper and cadmium contents as the treatment object, replaces the precipitated copper and cadmium with zinc powder without adjusting the pH value, introduces ultrasound during the replacement, reduces the amount of zinc powder by 26-35%, shortens the reaction time by 50%, realizes a high precipitation rate of copper and cadmium with a lower amount of zinc powder, and can still obtain a better removal efficiency of copper and cadmium by replacement reaction under room temperature and high pH conditions, and the neutral leachate of zinc roasted sand with copper and cadmium removed can be directly sent to the zinc electrowinning process, greatly reducing the production cost. In addition, the whole process is clean and efficient, meeting the requirements of clean production and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is the XRF image of the purified slag in Example 1 of the present invention;

[0020] Figure 2 It is the XRF image of the purified slag of Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0021] In order to make the purpose, technical solution and beneficial effects of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0022] The method for enhancing the replacement activity of zinc powder by ultrasonic wave in the process of zinc powder purification and copper and cadmium removal comprises the following steps:

[0023] (1) Zinc powder is slurried with dilute sulfuric acid, the liquid-to-solid ratio of zinc powder to dilute sulfuric acid is 1-6:1, the slurrying method is mechanical stirring, and the pH value of the zinc powder slurry is 5.0-5.4. The pH value of the zinc powder slurry is adjusted to be consistent with the neutral leaching solution of zinc roasted sand to avoid the addition of zinc powder affecting the pH value of the neutral leaching solution of zinc roasted sand.

[0024] (2) Add zinc powder slurry to the neutral leachate of zinc roasted sand, and replace copper and cadmium under ultrasonic conditions. The reaction temperature is 20-35°C. The zinc powder slurry is added in 1-10 times. The purpose of adding zinc powder multiple times is mainly: (1) to make the reaction more stable and avoid adding too much zinc powder at one time, which will cause the reaction to be too violent, so as to better control the reaction rate; (2) Adding a large amount of zinc powder at one time may cause local excessive zinc powder to agglomerate. In addition, excessive zinc powder at one time will cause the zinc powder to be wrapped by the generated basic salt due to local over-alkalinity, thereby triggering some side reactions and reducing the activity of zinc powder. Multiple additions can make the zinc powder more evenly distributed in the solution and reduce the occurrence of local excessive zinc powder. The last addition of zinc powder is 15-20 minutes away from the end of the reaction to ensure that the zinc powder reacts fully. The ultrasonic power is 30-600W.

[0025] (3) reacting for 30-180 min, liquid-solid separation, and obtaining a purified zinc roasted sand neutral leachate and filter residue from which copper and cadmium are removed. The copper and cadmium concentrations in the filtrate are analyzed by ICP-OES, and the copper and cadmium removal efficiencies are calculated.

[0026] In the zinc roasted sand neutral leaching solution, the copper ion concentration is 530-730 mg / L, and the cadmium ion concentration is 360-417 mg / L.

[0027] In step (2), the ultrasonic frequency is 19.4-19.8kHz and the power is 30-600W.

[0028] The zinc powder is industrial hydraulic atomized zinc powder, containing about 20wt% of water.

[0029] In order to more clearly illustrate the present invention, it is described in detail through the following examples.

[0030] In the following examples, the main components of the neutral leachate of zinc roasted sand are shown in Table 1.

[0031] Table 1 Main elements and contents of neutral leachate of zinc roasted sand

[0032]

[0033] Example 1

[0034] 3L of zinc roasted sand neutral leaching solution and 2.97 times the theoretical amount of copper and cadmium atomized zinc powder (the sum of the molar amounts of copper and cadmium is the theoretical amount of zinc powder, the same below) were measured and placed in a reactor and a beaker respectively.

[0035] Use sulfuric acid solution with pH=5.0-5.4 as slurry to slurry zinc powder and stir and mix, add the slurried zinc powder into the reactor of zinc roasted sand neutral leachate in 3 times, ultrasonic frequency 19.5kHz, ultrasonic power 120W, 25℃ for 30min. After the reaction, the mixture is filtered and separated, and the filter residue is placed in a vacuum drying oven at 60℃ for 18h. ICP-OES detection shows that the copper and cadmium concentrations in the filtrate are 4.67mg / L and 150mg / L, respectively, and the copper and cadmium removal rates are 99.36% and 58.35%, respectively.

[0036] The present invention relates to a method for enhancing the replacement activity of zinc powder in the process of zinc powder purification and copper and cadmium removal. The XRF of the purified slag is shown in Table 2, and the XRD pattern is shown in Figure 1 shown.

[0037] Table 2 Composition analysis of the purified slag obtained in Example 1

[0038] element Zn O S Cu Cd Fe Mn Mg As Content / wt.% 30.09 28.90 10.19 15.48 2.75 0.62 1.05 0.47 /

[0039] Comparative Example 1 (without ultrasound)

[0040] Except for not using ultrasound, other conditions in this comparative example are the same as those in Example 1.

[0041] The ICP-OES test showed that the concentrations of copper and cadmium in the filtrate were 29.39 mg / L and 246 mg / L, respectively, and the removal rates of copper and cadmium were 95.97% and 41.01%, respectively. The results showed that without ultrasound, the concentrations of copper and cadmium in the purified liquid increased, and the impurity removal efficiency was significantly reduced.

[0042] Comparative Example 2 (increasing the amount of zinc powder, increasing the reaction temperature, and not using ultrasound)

[0043] 3L of zinc roasted sand neutral leaching solution and 4 times the theoretical amount of copper and cadmium atomized zinc powder were measured and placed in a reactor and a beaker respectively.

[0044] Use sulfuric acid solution with pH=5.0-5.4 as slurry to slurry zinc powder and stir to mix. Add the slurried zinc powder into the reactor of zinc roasted sand neutral leachate in three times and react at 65℃ for 60min. After the reaction, filter the mixture and separate it, and dry the residue in a vacuum drying oven at 60℃ for 18h. ICP-OES test shows that the concentrations of copper and cadmium in the filtrate are 0.63mg / L and 200mg / L respectively, and the removal rates of copper and cadmium are 99.92% and 53% respectively. The results show that without ultrasound, even if the amount of zinc powder, reaction time and reaction temperature are increased, the removal rate of cadmium is still reduced.

[0045] The XRF of the purified slag is shown in Table 3, and the XRD pattern is shown in Figure 2 shown.

[0046] Table 3 Composition analysis of the purified slag obtained in Comparative Example 2

[0047] element Zn O S Cu Cd Fe Mn Mg As Content / wt.% 33.25 38.31 9.88 8.85 1.93 1.19 0.99 0.42 0.06

[0048] Comparative Example 3 (increasing the amount of zinc powder, increasing the reaction temperature, and not using ultrasound)

[0049] 3L of zinc roasted sand neutral leaching solution and 4 times the theoretical amount of copper and cadmium atomized zinc powder were measured and placed in a reactor and a beaker respectively.

[0050] Use sulfuric acid solution with pH=5.0-5.4 as slurry to slurry zinc powder and stir to mix. Add the slurried zinc powder into the reactor of zinc roasted sand neutral leachate three times and react at 25℃ for 30min. After the reaction, filter and separate the mixture, and place the filter residue in a vacuum drying oven at 60℃ for 18h. ICP-OES detection shows that the concentrations of copper and cadmium in the filtrate are 41.68mg / L and 245mg / L, respectively, and the removal rates of copper and cadmium are 94.29% and 41.25%, respectively. The results show that without ultrasound, even if the amount of zinc powder is increased, the removal rate of cadmium is still reduced. In the absence of ultrasound, the higher the temperature, the more conducive to the replacement of copper and cadmium.

[0051] Comparative Example 4 (increasing the reaction temperature)

[0052] The reaction temperature was raised to 65°C, and the rest was the same as in Example 1.

[0053] The ICP-OES test showed that the concentrations of copper and cadmium in the filtrate were 0.37 mg / L and 240 mg / L, respectively, and the removal rates of copper and cadmium were 99.95% and 43.6%, respectively. The results showed that under the conditions of the present invention, the removal rate of cadmium decreased with increasing reaction temperature, which may be because the pH of the solution decreased rapidly with increasing temperature, resulting in the reaction of some of the added zinc powder with H +The reaction reduces the amount of zinc powder that can undergo the replacement reaction, resulting in an incomplete reaction. In addition, the replaced cadmium will be redissolved when the temperature is increased, resulting in a decrease in the cadmium removal rate.

[0054] Comparative Example 5 (lowering reaction pH)

[0055] The pH values ​​of the zinc powder slurry and the zinc roasted sand neutral leaching solution were adjusted to 4.6-4.8, and the others were the same as in Example 1. The concentrations of copper and cadmium in the filtrate were 19.29 mg / L and 247 mg / L by ICP-OES detection, and the removal rates of copper and cadmium were 97.35% and 40.77%, respectively. The results showed that as the pH decreased, the removal rates of copper and cadmium decreased, mainly because the lower pH would cause the added zinc powder to react with H + After the reaction, the pH of the solution tends to be neutral, and if it is partially alkaline, it will regenerate basic salts and thus wrap. In addition, too low a pH will cause the displaced copper and cadmium to dissolve again in the solution, thereby reducing the removal rate.

[0056] Comparative Example 6 (lowering the reaction pH and increasing the reaction temperature)

[0057] The pH values ​​of the zinc powder slurry and the neutral leaching solution of zinc roasted sand were adjusted to 4.6-4.8, and the replacement reaction temperature was increased to 65°C. The other conditions were the same as those in Example 1. The concentrations of copper and cadmium in the filtrate were 25.48 mg / L and 258 mg / L, respectively, and the removal rates of copper and cadmium were 96.51% and 38.13%, respectively. The results showed that at a lower pH value, increasing the temperature was not conducive to the replacement of copper and cadmium by zinc powder, mainly because the increase in temperature would lead to a lower pH and more zinc powder would react with H + wasted.

[0058] Comparative Example 7 (lowering pH value, without ultrasound)

[0059] The pH values ​​of the zinc powder slurry and the zinc roasted sand neutral leaching solution were adjusted to 4.6-4.8, and no ultrasound was added during the replacement reaction. The rest was the same as in Example 1. ICP-OES detection showed that the concentrations of copper and cadmium in the filtrate were 16.05 mg / L and 188 mg / L, respectively, and the removal rates of copper and cadmium were 97.80% and 54.92%, respectively.

[0060] Example 2

[0061] 3L of supernatant and 1.8 times of the theoretical amount of copper and cadmium were measured and placed in a reactor and a beaker respectively. Then, a sulfuric acid solution with a pH of 5.0-5.4 was used as a slurry to slurry the zinc powder and mix the solid and liquid evenly. Then, the slurried zinc powder was added to the reactor containing the supernatant in 3 times, and finally reacted for 30 minutes at an ultrasonic power of 600W, an ultrasonic frequency of 19kHZ and 25°C. After the reaction, the mixture was filtered and separated, and the filter residue was placed in a vacuum drying oven at 60°C and dried for 18h. The concentrations of copper and cadmium in the filtrate were 69.17mg / L and 277mg / L, respectively, and the removal rates of copper and cadmium were 90.52% and 33.57%, respectively, as determined by ICP-OES.

[0062] Example 3

[0063] 3L of supernatant and 2.97 times of the theoretical amount of copper and cadmium were measured and placed in a reactor and a beaker respectively. Then, a sulfuric acid solution with a pH of 5.0-5.4 was used as a slurry to slurry the zinc powder and mix the solid and liquid evenly. Then, the slurried zinc powder was added to the reactor containing the supernatant twice, and finally reacted at 20kHZ ultrasonic frequency, 120W ultrasonic power and 35°C for 30min. After the reaction, the mixture was filtered and separated, and the filter residue was placed in a vacuum drying oven at 60°C and dried for 18h. The concentrations of copper and cadmium in the filtrate were 2.83mg / L and 141mg / L, respectively, and the removal rates of copper and cadmium were 99.61% and 66.19%, respectively, as determined by ICP-OES.

[0064] Example 4

[0065] 3L of supernatant and 2.97 times of the theoretical amount of copper and cadmium were measured and placed in a reactor and a beaker respectively. Then, a sulfuric acid solution with a pH of 5.0-5.4 was used as a slurry to slurry the zinc powder and mix the solid and liquid evenly. Then, the slurried zinc powder was added to the reactor containing the supernatant twice, and finally reacted at 120W ultrasonic power and 38°C for 30 minutes. After the reaction, the mixture was filtered and separated, and the filter residue was placed in a vacuum drying oven at 60°C and dried for 18 hours. The concentrations of copper and cadmium in the filtrate were 1.15mg / L and 170mg / L, respectively, and the removal rates of copper and cadmium were 99.84% and 58.91%, respectively, as determined by ICP-OES.

[0066] Example 5

[0067] Measure 3L of supernatant and 4 times the theoretical amount of copper and cadmium atomized zinc powder and place them in a reactor and a beaker respectively. Then use a sulfuric acid solution with a pH of 5.0-5.4 as a slurry to slurry the zinc powder and mix the solid and liquid evenly. Then add the slurried zinc powder to the reactor containing the supernatant twice, and finally react for 30 minutes at an ultrasonic power of 120W and 35°C. After the reaction, the mixture is filtered and separated, and the filter residue is placed in a vacuum drying oven at 60°C and dried for 18 hours. The concentrations of copper and cadmium in the filtrate are 0.1mg / L and 117mg / L respectively, and the removal rates of copper and cadmium are 99.99% and 71.94% respectively by ICP-OES detection.

[0068] Finally, it should be noted that the above preferred embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail through the above preferred embodiments, those skilled in the art should understand that various changes can be made in form and details without departing from the scope defined by the claims of the present invention.

Claims

1. A method for enhancing the replacement activity of zinc powder by using ultrasound during the process of zinc powder purification and copper and cadmium removal, characterized in that: The following steps are involved: (1) Use dilute sulfuric acid to slurry zinc powder. The pH value of the zinc powder slurry is 5.0-5.4; (2) Add zinc powder slurry into zinc roasted sand neutral leaching solution, and replace and remove copper and cadmium under ultrasonic conditions at a reaction temperature of 20-40°C; (3) Liquid-solid separation to obtain a purified zinc roasted sand neutral leaching solution from which copper and cadmium are removed.

2. The method for enhancing the replacement activity of zinc powder by using ultrasound in the process of zinc powder purification and copper and cadmium removal according to claim 1, characterized in that: In the zinc roasted sand neutral leaching solution, the copper ion concentration is 530-730 mg / L, and the cadmium ion concentration is 360-417 mg / L.

3. The method for enhancing the replacement activity of zinc powder by using ultrasound in the process of zinc powder purification and copper and cadmium removal according to claim 1, characterized in that: In step (1), the liquid-to-solid ratio of zinc powder to dilute sulfuric acid is 1-6:1, and the slurrying method is mechanical stirring.

4. The method for enhancing the replacement activity of zinc powder by using ultrasound in the process of zinc powder purification and copper and cadmium removal according to claim 1, characterized in that: In step (2), the zinc powder slurry is added in portions.

5. The method for enhancing the replacement activity of zinc powder by using ultrasound in the process of zinc powder purification and copper and cadmium removal according to claim 4, characterized in that: The last addition of zinc powder is 15-20 minutes away from the end of the reaction.

6. The method for enhancing the replacement activity of zinc powder by using ultrasound in the process of zinc powder purification and copper and cadmium removal according to any one of claims 1 to 5, characterized in that: The amount of the pure zinc powder added is 1.8-4 times the total molar amount of copper and cadmium in the neutral leaching solution of zinc roasted sand.

7. The method for enhancing the replacement activity of zinc powder by using ultrasound in the process of zinc powder purification and removal of copper and cadmium according to any one of claims 1 to 5, characterized in that: The ultrasonic frequency is 19.4-19.8kHz and the power is 30-600W.

8. The method for enhancing the replacement activity of zinc powder by using ultrasound in the process of zinc powder purification and copper and cadmium removal according to any one of claims 1 to 5, characterized in that: The zinc powder is industrial hydraulic atomized zinc powder.

Citation Information

Patent Citations

  • Wet zinc metallurgical ultrasound purification method, device and use

    CN101392328A

  • Method of utilizing low-consumption zinc powder to purify zinc sulfate solution

    CN110819803A

  • Purification and cadmium removal method for zinc hydrometallurgy

    CN113667833A

  • Method for deeply purifying and removing copper and cadmium through combination of ultrasonic waves and inert wet grinding for strengthening zinc hydrometallurgy

    CN114182108A

  • Method for purification and nickel, cobalt, and germanium removal of aqueous zinc sulfate solution

    WO2021147816A1